Feeding Practices of Colombian Families with Minors Younger than 18 Years during the Initial Phase of COVID-19 Quarantine - Dadán, Silvana; Higuera-Carrillo, Michelle; Camacho-Cruz, Jhon; Daza-Carreño, Wilson (Journal of Child Science, 2024)
The coronavirus disease 2019 (COVID-19) pandemic has raised concerns regarding food availability and access. The aim of this study is to describe feeding practices and associated factors in Colombian families with members younger than 18 years at the beginning of the 2020 quarantine. This is an observational, descriptive, cross-sectional study. An online survey was administered to parents or caregivers of minors younger than 18 years in Colombia, focusing on feeding practices. The analysis consisted of three steps: first, estimation of descriptive statistics; second, multiple correspondence analysis to derive an index for each main meal; and finally, generalized linear models were applied to each main meal index, incorporating predictors to explain changes in food consumption. A total of 1,419 participants were included. Among them, 654 (46%) indicated changes in their feeding practices during the quarantine due to reasons such as lack of funds, portion reduction to stretch food, difficulty in shopping, and perception of limited variety in the market. The perceived lack of variety while shopping significantly affected the breakfast index (p = 0.037), lunch index (p = 0.037), and dinner index (p = 0.001). Socioeconomic level influenced the breakfast index (p = 0.012) and lunch index (p = 0.012) but not the dinner index. Nearly half of the surveyed families perceived changes in their feeding practices during the COVID-19 pandemic, which were linked to socioeconomic status and the perceived lack of variety while shopping.
Keywords: coronavirus; nutrition; surveys; programs; policies; food security